Mathematical Anxiety and Resilience as an Influence of Mathematical Literacy Skills - Bilhaki, Raden Roafli; Faradillah, Ayu (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Mathematical literacy is essential for applying mathematical concepts to real-life problems, yet its development is often hindered by psychological factors such as anxiety and resilience. Mathematics anxiety negatively affects students' cognitive and problem-solving abilities, while resilience supports emotional regulation and sustained learning. This study aims the combined influence of mathematics anxiety and resilience on students’ mathematical literacy. The research method used was qualitative with a phenomenological approach. Subsequently, using Winsteps on the Wright Map table, three students were selected from a population of 128 grade XII students to become research subjects. The three subjects were selected based on the categories of mathematical anxiety and resilience. The results of the study indicate that students with high anxiety levels and low resilience have lower mathematics literacy scores. They are unable to complete all the ability indicators. Similarly, students with moderate anxiety and moderate resilience also showed low literacy scores. They were able to complete questions on the comprehension and representation indicators. Conversely, students with low anxiety and high resilience showed higher mathematical literacy scores, indicating that resilience plays a key role in overcoming anxiety and improving performance in mathematical tasks.